Age-related changes in the levels and kinetics of pulmonary cytokine and chemokine responses to Streptococcus pneumoniae in mouse pneumonia models. (November 2018) - Janesch, Philipp; Stulik, Lukas; Rouha, Harald; Varga, Cecilia; Steinhäuser, Jacqueline; Zerbs, Manuel; Nagy, Eszter
Highlights: Aging increases vulnerability to S. pneumoniae pneumonia in murine models. Pulmonary cytokine and chemokine kinetics greatly differ in aged and young mice. Impaired bacterial control in aged mice parallels delayed IFN-γ related responses. Resolution of inflammation in young mice correlates with pneumococcal clearance. Abstract: Streptococcus pneumoniae is a major human pathogen at the extremes of age. The elderly are particularly vulnerable to S. pneumoniae, the most common causative agent of bacterial pneumonia in this population. Despite the availability of vaccines and antibiotics, mortality rates associated with pneumococcal pneumonia in this age group remain high. In light of globally increasing life-expectancy, a better understanding of the patho-mechanisms of elderly pneumococcal pneumonia, including alterations in innate immune responses, is needed to develop improved therapies. In this study we aimed at investigating how increased susceptibility to pneumococcal infection relates to inflammation kinetics in the aged mouse pneumonia model by determining pulmonary cytokine and chemokine levels and comparing these parameters to those measured in young adult mice. Firstly, we detected overall higher pulmonary cytokine and chemokine levels in aged mice. However, upon induction of pneumococcal pneumonia in aged mice, delayed production of certain analytes, such as IFN-γ, MIG (CXCL9), IP-10 (CXCL10), MCP-1 (CCL2), TARC (CCL17) and MDC (CCL22) became apparent. In addition, aged mice were unable to control excess inflammatory responses: while young mice showed peak inflammatory responses at 20 h and subsequent resolution by 48 h post intranasal challenge, in aged mice increasing cytokine and chemokine levels were measured. These findings highlight the importance of considering multiple time points when delineating inflammatory responses to S. pneumoniae in an age-related context. Finally, correlation between pulmonary bacterial burden and cytokine or chemokine levels in young mice suggested that appropriately controlled inflammatory responses support the host to fight pneumococcal infection.